2016
DOI: 10.1186/s12870-016-0819-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis provides novel insight into the interaction between resistant vs susceptible tomato cultivars and TYLCV infection

Abstract: BackgroundTomato yellow leaf curl virus (TYLCV) is a member of the family Geminiviridae, genus Begomovirus. The virus is a widespread plant virus that causes important economic losses in tomatoes. Genetic engineering strategies have increasingly been adopted to improve the resistance of tomatoes to TYLCV.ResultsIn this study, a proteomic approach was used to investigate the molecular mechanisms involved in tomato leaf defense against TYLCV infection. Proteins extracted from leaves of resistant tomato cultivar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Derived from T5678161-1-1-2-2 and T07-018, ‘Zheza-301’ was bred to resist to TYLCV infection with the Ty-2 locus. ‘Jinpeng-1’, a hybrid of Holland tomato cultivar 99-13A and 9708B from America, was susceptible to TYLCV infection [ 6 ]. Seeds of ‘Jinpeng-1’ and ‘Zheza-301’ were obtained from Xi’an Jinpeng Seed Co., Ltd. and the Institute of Vegetables, Zhejiang Academy of Agricultural Sciences, respectively [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Derived from T5678161-1-1-2-2 and T07-018, ‘Zheza-301’ was bred to resist to TYLCV infection with the Ty-2 locus. ‘Jinpeng-1’, a hybrid of Holland tomato cultivar 99-13A and 9708B from America, was susceptible to TYLCV infection [ 6 ]. Seeds of ‘Jinpeng-1’ and ‘Zheza-301’ were obtained from Xi’an Jinpeng Seed Co., Ltd. and the Institute of Vegetables, Zhejiang Academy of Agricultural Sciences, respectively [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intact virions pass through the food canal in the stylet of B. tabaci and reach the esophagus; they then move through the plant phloem as B. tabaci inserts its proboscis and feeds on infected tomato leaves [ 4 , 5 ]. Upon entering plant host cells, the DNA of TYLCV replicates via a rolling circular mechanism [ 6 ]. Host enzymes can convert the incoming geminivirus ssDNA to double-stranded DNA (dsDNA) that serves as a transcription template.…”
Section: Introductionmentioning
confidence: 99%
“…SAMs catalyze the biosynthesis of S-adenosylmethionine (SAM) from methionine and ATP, and they are active in the biosynthesis of lignin, glycine betaine and polyamines (Fontecave et al, 2004). These proteins can be induced by various environmental stresses, such as cold, salt, drought stress and even pathogen infection (Li et al, 2013a; Huang et al, 2016), and most of them were down-regulated by stress (Wang et al, 2016; Yuan et al, 2016). This outcome was consistent with the results showing that the inoculation of FOC significantly decreased SAMs expression (Table 2, Figure 5C; Supplementary Figures 4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…Total root protein was isolated from infected cucumber roots of the susceptible bulk and resistant bulk of cucumber generation F2, and the result showed that jasmonic acid and redox signaling components occurred in response to F. oxysporum infection in resistant plants (Zhang et al, 2016). Eighty-six differentially expressed proteins were identified from the leaves of resistant tomato cultivar “Zheza-301” and susceptible cultivar “Jinpeng-1” after TYLCV infection, which demonstrated that an interaction network between tomato leaves and TYLCV infection was established (Huang et al, 2016). To date, although several papers have addressed the use of proteomics to investigate the interactions of plants and pathogens (Konishi et al, 2001; Wang et al, 2011; Carrillo et al, 2014) or plants and PGPR (Kandasamy et al, 2009; Wang et al, 2013), little research is available on the effects of PGPB on cucumber plants under pathogenic attack.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chloroplasts, peroxisomes are a site of ROS production, which is essential for plant defense by HR establishment, local PCD, and activation of plant defense genes. Peroxisomes work in the C2 cycle producing ROS by the activity of glycolate oxidase enzyme (Huang et al 2010;Liu et al 2013;Huang et al 2016). Regarding the two crucial functions displayed by peroxisome in plant defense;…”
Section: Peroxisomes -Power To Virusesmentioning
confidence: 99%